2007
DOI: 10.3354/meps06933
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of shallow-water juvenile flatfish nursery grounds: application of the self-thinning rule

Abstract: Annual development of density and mean weight of juvenile plaice Pleuronectes platessa was examined at 2 nursery grounds (Port Erin Bay, Isle of Man, Irish Sea and Admucknish Bay, Firth of Lorne, west coast of Scotland) over a number of years. In both cases there was evidence of 'self-thinning' in the populations when the density was high, although in Port Erin Bay the slope suggested a relationship different from the standard -4 ⁄ 3 rule proposed for animal populations. The site specific dynamic thinning line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 43 publications
4
29
0
Order By: Relevance
“…m −2 corrected for catchability). These values are within the range of previous estimates reported from this site (Burrows et al 2001, Nash et al 2007). For means computed from n multiple transects, precision improves as (√ ⎯n) -1 .…”
Section: Taqman Results From Fishsupporting
confidence: 80%
“…m −2 corrected for catchability). These values are within the range of previous estimates reported from this site (Burrows et al 2001, Nash et al 2007). For means computed from n multiple transects, precision improves as (√ ⎯n) -1 .…”
Section: Taqman Results From Fishsupporting
confidence: 80%
“…Available resources can be affected by exploitative competition between individuals, either of the same or different species. Studies with plaice point to a lack of intraspecific competition for food (Van der Veer et al 2010) and for Irish Sea populations, it is even suggested that the carrying capacity of nursery grounds for plaice is rarely approached (Nash et al 2007). However, interactions within the benthicfeeder assemblage (other fish and invertebrates) can modify the carrying capacity and trajectories for individual species (Gibson 1994, Nash et al 2007).…”
Section: Habitat Quality Of Flatfish Nursery Areasmentioning
confidence: 99%
“…Studies with plaice point to a lack of intraspecific competition for food (Van der Veer et al 2010) and for Irish Sea populations, it is even suggested that the carrying capacity of nursery grounds for plaice is rarely approached (Nash et al 2007). However, interactions within the benthicfeeder assemblage (other fish and invertebrates) can modify the carrying capacity and trajectories for individual species (Gibson 1994, Nash et al 2007). An analysis similar to the one applied in this study has suggested that in sand gobies Pomatoschistus minutus occurring sympatrically with juvenile flatfish during summer, growth is close to the maximum possible across their distribution range (Freitas et al 2011), suggesting a competitive advantage.…”
Section: Habitat Quality Of Flatfish Nursery Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…These quantities are closely related to physiological mortality rate (Beyer 1989) [m µ j (m)]/g j (m), the importance of which has been recognized by theorists (Cushing 1975;Werner and Gilliam 1984;Beyer 1989;) and empiricists (Houde 1987;Houde and Zastrow 1993;Bohlin et al 1994;Houde 1997;Nash et al 2007;Nash and Geffen 2012) alike.…”
Section: Methodsmentioning
confidence: 99%